2018
DOI: 10.3390/en11102559
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of PEO-PMMA-LiClO4-Based Solid Polymer Electrolytes Containing Silica Aerogel Particles for All-Solid-State Lithium Batteries

Abstract: To improve the ionic conductivity and thermal stability of a polyethylene oxide (PEO)-ethylene carbonate (EC)-LiClO4-based solid polymer electrolyte for lithium-ion batteries, polymethyl methacrylate (PMMA) and silica aerogel were incorporated into the PEO matrix. The effects of the PEO:PMMA molar ratio and the amount of silica aerogel on the structure of the PEO-PMMA-LiClO4 solid polymer electrolyte were studied by X-ray diffraction, Fourier-transform infrared spectroscopy and alternating current (AC) impedan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 40 publications
(50 reference statements)
0
26
0
Order By: Relevance
“…[5][6][7][8][9] However, the low room temperature conductivity (10 À7 to 10 À6 S cm À1 ), narrow electrochemical windows and inferior mechanical properties of PEO are the main obstacles for further development. 4,7,9 Blending is one of the valid approaches to ameliorate the properties of PEO, such as with PVP, 10 PVDF, 11 and PMMA; 12 this can decrease crystallization and enhance the fractional movement of polymer chains and the migration amount of Li + . 13 Similar to PEO, polyvinyl alcohol (PVA) is another semicrystalline polymer with the fascinating properties of nontoxic, water solubility and biocompatibility; it has been under the spotlight and applied as an electrolyte in supercapacitors on a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] However, the low room temperature conductivity (10 À7 to 10 À6 S cm À1 ), narrow electrochemical windows and inferior mechanical properties of PEO are the main obstacles for further development. 4,7,9 Blending is one of the valid approaches to ameliorate the properties of PEO, such as with PVP, 10 PVDF, 11 and PMMA; 12 this can decrease crystallization and enhance the fractional movement of polymer chains and the migration amount of Li + . 13 Similar to PEO, polyvinyl alcohol (PVA) is another semicrystalline polymer with the fascinating properties of nontoxic, water solubility and biocompatibility; it has been under the spotlight and applied as an electrolyte in supercapacitors on a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, it is shown that the addition of inorganic particle into the polymer matrix greatly enhances the ionic conductivity and lithium transference number of traditional electrolytes system. CPEs not only has a greater ionic conductivity and lithium transference number than traditional polymer electrolytes system, but several recent studies also show that CPEs exhibit better thermal stability and energy density [16,32].…”
Section: Discussionmentioning
confidence: 99%
“…Qian et al [8] reported an improvement in ionic conductivity from 1.30×10 -7 S/cm for (PEO) 16 LiClO 4 to 2.36×10 -4 S/cm at room temperature when 50 wt% Ethylene Carbonate (EC) was incorporated into the mixture. The addition of plasticizers lowers the glass transition temperature, T g of the mixture, and this decreases the degree of crystallinity of polymer electrolytes at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13a). To improve the ionic conductivity and thermal stability of a polyethylene oxide-type SSE for LIBs, Lim et al109 incorporated poly (methyl methacrylate) into polyethylene oxide matrix. The…”
mentioning
confidence: 99%